ANALISIS DAYA DUKUNG LAHAN PERTANIAN SEBAGAI UPAYA MENDUKUNG KETERSEDIAAN PANGAN DI KAWASAN SLEMAN TENGAH - Sarastika, Tiara; Anggrasari, Herdiana (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
The Central Sleman area is a peri-urban area directly adjacent to Yogyakarta, making land conversion increasingly prevalent and unavoidable. In comparison, the Central Sleman area has a role as one of the food barns due to fertile land conditions and is suitable for agriculture. Intensive conversion of agricultural land to non-agricultural land will result in the loss of productive agricultural land, resulting in decreased rice production. This will result in high rice imports and reduced employment in the agricultural sector. This research aims to analyze the development of agricultural land use, its projection, and the carrying capacity of agricultural land in the Central Sleman Region. The calculation of the agricultural land carrying capacity is based on Odum, Howard, and Issard. The results showed that the Central Sleman Area has a decreasing rate of change in the agricultural land area every year in Kapanewon. The calculation results of agricultural land's carrying capacity show that in 2020, land's carrying capacity exceeded 0.83. The results of the projection calculation in 2024 found that 4 out of 5 Kapanewon in the Central Sleman Region cannot achieve food self-sufficiency. Therefore, efforts are needed to increase the carrying capacity of agricultural land, mainly through increasing the productivity of food crops and protecting agricultural land from land conversion.